Stages in the Help-Seeking Decision-Making Process and Factors Involved - Setiawan, Jenny Lukito (Faculty of Psychology, Universitas Surabaya, 2011)
This paper describes a study designed to investigate stages in the help-seeking decision making process and factors involved. A multi-method design was adopted which involved 1,279 respondents. Results found that there was a hierarchical system in coping behaviour. Respondents tried to face their problems on their own before seeking help. Internal resources and problem perceived, social impacts, and personal characteristics were involved in help-seeking decision process. Personal qualities of and familiarity with the potential helpers, perceived capacity to help, social role and the accessibility of the potential helpers, guarantee of confidentiality were considered in the selection of helpers. Artikel ini memaparkan suatu studi yang menggali tahap-tahap proses pembuatan putusan mencari-bantuan dan faktor-faktor yang terlibat. Diadopsi sebuah desain multi-metode yang menyertakan 1,279 responden. Hasil mengungkapkan adanya sistem hierarki dalam perilaku coping. Para responden mencoba menghadapi sendiri masalahnya sebelum mencari bantuan. Sumber-sumber internal dan masalah yang dipersepsi, dampak sosial, dan cirri-ciri personal terlibat dalam proses pembuatan putusan dalam mencari-bantuan. Kualitas pribadi dan sudah dikenalnya penolong potensial, perkiraan kapasitasnya, peran sosial dan mudahnya menemui penolong yang potensial, serta jaminan kerahasiaan, dipertimbangkan dalam memilih para penolong.